Click Chemistry, A Potent Tool in Medicinal Sciences - Musumeci, F.; Schenone, S.; Desogus, A.; Nieddu, E.; Deodato, D.; Botta, L. (Current Medicinal Chemistry, 2015)
This review focuses on the application of click chemistry in medicinal sciences, and particularly on its role in drug discovery. Because of its high modularity, click chemistry helps to accelerate the current drug discovery process, which relies on massive screening of chemical libraries. This article describes examples of click chemistry applications that are aimed at finding new lead candidates against pathologies such as cancer, AIDS and Alzheimer’s disease, and explores the impact that the technique could have in therapy and prevention in the near future, through application in drug delivery systems, bioconjugation and diagnostic. An introduction, addressed to researchers who intend to use this methodology, examines the opportunities to perform click reactions according to the most common and best studied techniques, such as synthesis in water, on solid phase, and under microwave or ultrasound irradiation. Every topic is furnished with examples which have appeared in the literature in the last five years and is clarified by schemes and figures.
Keywords: drug discovery